INTERACTIVE EFFECTS OF SPAN LENGTH AND RAFTER ANGLE ON THE DUCTILITY AND STABILITY OF STEEL WAREHOUSE STRUCTURES - Darmawan, Kevin Candra; Suswanto, Budi; Amalia, Aniendhita Rizki (Institut Teknologi Sepuluh Nopember, 2025)
The warehouse frame is a specialized steel structure requiring more complexcalculations than standard portal frames. This study investigates the impact ofrafter angle and span length on ductility and stability. Results indicate thatincreasing span length enhances ductility but reduces stability due to higher storydrift. For example, M1 (10-meter span) shows a ductility of 4.62 and story drift of13.64 mm, while M3 (20-meter span) achieves 5.07 (+9.62%) with a drift of 46.77mm. A larger rafter angle slightly increases ductility but decreases stability. M1 (10°angle) records 4.62 ductility and 13.64 mm drift, whereas M7 (20° angle) reaches4.71 (+1.79%) with 16.92 mm drift. Higher structure stiffness reduces ductility butboosts stability. M3 (128.29 kN/m stiffness) shows 5.07 ductility and 46.77 mmdrift, while M12 (192.67 kN/m) records 4.96 (-2.17%) with 29.68 mm drift. DespiteM12's minor ductility reduction, M3 demonstrates better elastic-plastic behavior.These findings reveal a clear polarity between ductility and stability